Constraints on anomalous Higgs boson couplings using production and decay information in the four-lepton final state - Sirunyan,AM; Collaboration,CMS; Tumasyan,A; Adam,W; Ambrogi,F; Asilar,E; Bergauer,T; Brandstetter,J; Brondolin,E; Dragicevic,M; Ero,J; Flechl,M; et al. (PHYSICS LETTERS B, 2017)
AsearchisperformedforanomalousinteractionsoftherecentlydiscoveredHiggsbosonusingmatrixelementtechniqueswiththeinformationfromitsdecaytofourleptonsandfromassociatedHiggsbosonproductionwithtwoquarkjetsineithervectorbosonfusionorassociatedproductionwithavectorboson.ThedatawererecordedbytheCMSexperimentattheLHCatacenter-of-massenergyof13TeVandcorrespondtoanintegratedluminosityof38.6fb−1.Theyarecombinedwiththedatacollectedatcenter-of-massenergiesof7and8TeV,correspondingtointegratedluminositiesof5.1and19.7fb−1,respectively.AllobservationsareconsistentwiththeexpectationsforthestandardmodelHiggsboson.